Correlation between Learning style and achievement in Physics Learning. Issue 1 (June 2021) - Halim, A; Wahyuni, A; Susanna,; Elisa,; Hamid, A.; Irwandi,
Abstract: This study aims to determine the relationship between learning styles and student learning outcomes in physics subjects. The research using survey techniques and documentation with using questionnaires and documentation method for data collection. Questionnaires are used to obtain data of learning style variables, while documentation is used to obtain data of learning outcomes variables. The results of data analysis, with the product moment correlation technique, show that there is a correlation of positive and significant relationship between learning styles and student learning outcomes in physics course. In addition, the results of the study also showed that the greatest contribution of learning styles to learning outcomes was in analytic and holistic learning styles.